2020
DOI: 10.1186/s12909-020-1954-7
|View full text |Cite
|
Sign up to set email alerts
|

“Evaluation of a best practice approach to assess undergraduate clinical skills in Paediatrics”

Abstract: Background: The Objective Structured Clinical Examination (OSCE) has been used in pediatrics since the 1980s. Its main drawback is that large numbers of children are needed to make up for the fatigue factor inherent in prolonged testing periods. Also, examinations mainly include children between 7 and 16 years old. We describe the summative examination used in our institution to evaluate medical students' clinical competencies in pediatrics with realistic available resources and for a wider age-range. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…believe that one of the proper evaluation methods to assess the clinical skills of the students is the OSCE method which has appropriate criteria for clinical evaluation of the students. [ 29 30 31 ] The results of the study by Gandomkar and Amini also showed that among the clinical skills evaluation tests, OSCE test is the most used test in the clinical medical courses in Iran. [ 32 33 34 ] Results of the study by Rafiee et al .…”
Section: Discussionmentioning
confidence: 99%
“…believe that one of the proper evaluation methods to assess the clinical skills of the students is the OSCE method which has appropriate criteria for clinical evaluation of the students. [ 29 30 31 ] The results of the study by Gandomkar and Amini also showed that among the clinical skills evaluation tests, OSCE test is the most used test in the clinical medical courses in Iran. [ 32 33 34 ] Results of the study by Rafiee et al .…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be explained by the fact that medical students taking the exam in May have less overall clinical experience. [17] Comparing e-learning and traditional seminars To compare the e-learning and lecture formats, two e-learning modules (on constipation and gastroesophageal re ux) were taught exclusively using traditional seminars (the 2016-17 academic intake) and exclusively using e-learning modules (the 2017-18 academic intake). Seminars were given by the authors of the e-learning modules so as to maximize similarities between the learning content in the seminars and e-learning modules.…”
Section: Pediatric Exam Evaluation Methodsmentioning
confidence: 99%
“…Experimental questions ( Figure 1 ) were asked in the same session of the following year to avoid a "session effect", as we had previously shown in a retrospective study that our students were more likely to get higher scores in exams taken in the second session (January) than in the first (May). This difference could be explained by the fact that medical students taking exams in May have less overall clinical experience 18 .…”
Section: Factors Influencing Scores In Subjects Taught Using E-learningmentioning
confidence: 99%